Central Stars of Planetary Nebulae in Galactic Open Clusters: Providing additional data for the White Dwarf Initial-to-Final-Mass Relation. Issue Volume 14:Issue S343(2019) (August 2018) - Fragkou, Vasiliki; Parker, Quentin A.; Zijlstra, Albert; Shaw, Richard; Lykou, Foteini
Abstract: Accurate (< 10%) distances of Galactic star clusters allow a precise estimation of the physical parameters of any physically associated Planetary Nebula (PN) and also that of its central star (CSPN) and its progenitor. The progenitor's mass can be related to the PN's chemical characteristics and, furthermore, provides additional data for the widely used white dwarf (WD) initial-to-final mass relation (IFMR) that is crucial for tracing the development of both carbon and nitrogen in entire galaxies. To date, there is only one PN (PHR1315- 6555) confirmed to be physically associated with a Galactic open cluster (ESO 96 -SC04) that has a turn-off mass ∼2Mʘ . Our deep HST photometry was used for the search of the CSPN of this currently unique PN. In this work, we present our results.